A rare case of Creutzfeldt‐Jakob disease reported from Nepal. Issue 9 (13th September 2021) - Neupane, Durga; Gupta, Prashant Kumar; Subedi, Sushil Sharma; Gupta, Dilip; Chhetri, Sunit
Abstract: Creutzfeldt‐Jakob disease, though rare, should be considered in the clinical picture of rapidly progressive dementia and absence of verbal response as evident in our case despite the absence of typical radiological picture. Abstract : Creutzfeldt‐Jakob disease, though rare, should be considered in the clinical picture of rapidly progressive dementia and absence of verbal response as evident in our case despite the absence of typical radiological picture.